Dualitas Gender Dan Ambiguitas Identitas Dalam Love And Death In Bali Karya Vicki Baum - Nailul Ulah Al Chumairoh Machfud; Philosa Kasyutiantara Denpabhara (Journal of Innovative and Creativity, 2025)
This study examines the representation of gender duality and identity ambiguity in Vicki Baum’s novel Love and Death in Bali through the lenses of queer theory and intersectional feminism. Using a qualitative textual analysis approach, the research reveals that characters, especially Raka and Alit, exhibit fluid gender identities that defy the traditional masculine-feminine binary. Their bodily descriptions, clothing, and emotional expressions reflect gender performativity that challenges patriarchal norms both within Balinese customs and under Dutch colonial power. Additionally, the position of women in the novel is portrayed as oppressed by the overlapping forces of traditional authority and colonial domination, particularly through the regulation of their bodies and sexuality. This analysis argues that Love and Death in Bali not only documents the historical colonial reality but also opens critical discursive space about gender identity as complex, fractured, and political. By combining queer and intersectional perspectives, this study highlights the importance of rereading colonial literature as a site for producing meanings of identity that are fluid and unstable.